Pengembangan dan Pelestarian Produk Budaya Udeng Kota Batu - Shannaz Mutiara Deniar; Yeyen Pratika (Universitas Islam Indonesia, 2021)
Batu City is one of the tourist destinations in Indonesia. In addition to very diverse tourist destinations, Batu City also has cultural characteristics that are very close to the community so that it can be used as an identity. For this reason, this community service focuses on the development and preservation of cultural products found in Batu City. This program associates with the Paguyuban Sangga Braja. This association has a very high concern for cultural products, especially the traditional headband or known as udeng. Udeng designed by the community is based on the history, philosophy, topography and local wisdom of Batu City. Although this udeng has received recognition from the local government, but the information and public awareness about this udeng is still very lacking. In fact, this association expects that this product can be used as a characteristic of Batu City as a tourist city that has a cultural identity. To overcome this problem, the solution offered is to digitalize this batik pattern of udeng and the registration for copyright.